THERAPEUTIC PERSPECTIVE VIEW OF ANTIMICROBIAL PEPTIDES - PRITI BALA; JAINENDRA KUMAR; NAVIN KUMAR (International Journal of Pharma and Bio Sciences, 2014)
Due to increasing antibiotic resistance by pathogenic bacteria, it has become necessary to develop new antimicrobial molecules as therapeutic agents to overcome this problem. Antimicrobial peptides from different organisms can serve as the natural defense molecules to combat these pathogenic microorganisms. These are small cationic peptides with diverse range of antimicrobial activity that thwart resistance by bacteria.